2020
DOI: 10.5430/rwe.v11n1p20
|View full text |Cite
|
Sign up to set email alerts
|

Incentive Function of Audit Opinion for the Increase of Regional Operational Expenditure and Own-Source Revenues Through Sensitivity Analysis in Indonesia

Abstract: This study aims to analyze the sensitivity testing using measurements of realization of regional own-source revenues and operating expenditure and to analyze the extent of the effect of sample differences between Java and non-Java provinces by using samples outside of Java. By using sensitivity analysis, the results found the influence of audit opinion on the performance of the provincial government mediated by the realization of regional operating expenditure. More specifically, when using the measurement of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Liu & Lin (2012) found that the audit findings presented by the auditors have a positive effect on the level of corruption in China, where efforts to improve the post- audit findings can reduce the level of corruption that occurs. In order to encourage an increase in the target of unqualified opinions, it is expected that the central government can provide incentive funds to regional governments that get unqualified opinions to maximize their capacity to increase financial accountability (Abdullah et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Liu & Lin (2012) found that the audit findings presented by the auditors have a positive effect on the level of corruption in China, where efforts to improve the post- audit findings can reduce the level of corruption that occurs. In order to encourage an increase in the target of unqualified opinions, it is expected that the central government can provide incentive funds to regional governments that get unqualified opinions to maximize their capacity to increase financial accountability (Abdullah et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…According to the 1945 Constitution, the institution assigned the task of auditing state and regional finances is the Financial Audit Agency (BPK) According to Table 1.1, 83 percent of LKPDs received a WTP opinion between 2016 and 2020. Audit opinions reflect the performance of local governments in realizing regional operational expenditures (Abdullah et al, 2020;Kahar et al, 2023). The quality of Local Government Financial management can maintain the economic stability of a region (Craja et al, 2020;Mabelane et al, 2023).…”
Section: Introductionmentioning
confidence: 99%